Monopolar transurethral resection of the prostate for benign prostatic hyperplasia: What are the outcomes and complications in our patients? - I C Akpayak; S I Shuaibu; V E Onowa; L E Nabasu; Z Z Galam (Nigerian Journal of Medicine, 2017)
BACKGROUND: Transurethral resection of the prostate (TURP) is the current gold standard for the operative management of symptomatic Benign prostatic hyperplasia (BPH) and has excellent long term efficacy. Currently there is a gradual shift towards bipolar TURP and Holmium enucleation of the prostate (HoLEP) due to fear of complications, particularly transurethral resection (TUR) syndrome associated with monopolar TURP. However, bipolar generator and high powered holmium laser resectoscpe remain very expensive and make the bipolar TURP/HoLEP out of reach for majority of our patients.This study seeks to review our experience with monopolar TURP with a view to appraising its outcomes and complications seen in our patients. PATIENTS AND METHODS: Records of 42 patients, who underwent monopolar TURP for BPH between October, 2013 and September, 2016 were reviewed retrospectively.The data of patients who had undergone monopolar TURP,following standardized technique,were retrieved and subjected to statistical analysis. RESULTS: The mean age of the 42 patients was 67.07±9.38 (range 51 – 86).Those in the age range 60-69 years had most of the procedure.The mean prostate volume was 70±23.74 (ml);the mean prostate specific antigen (PSA) was 5.32±5.4ng/ml. All the patients had spinal anaesthesia.The mean intraoperative time was 71.05±19.07 (mins), awhile the mean hospital stay for the patients was 61.14±27.13 (hrs).The mean volume of 5% dextrose-water used for irrigation at surgery was 30L.Most of the patients,33(78.6%) had their catheters removed at 3-5 postoperative days. Only, 9(21.4%) had catheter for more than 5 days.The mean weight of resected prostatic chips was 29±9.2g. Intraoperatively, 1(2.4%) patient had bleeding that needed blood transfusion, 6(14.3%) had capsular perforations while none of our patients had TUR syndrome. Postoperatively, 3(7.2%) patients had clot retention while 2(4.8%) had UTI and 32(76%) had retrograde ejaculation. All patients except 1(2.4%) had satisfactory voiding at removal of catheter and subsequent follow up visits. CONCLUSION: Improved antibiotics, perioperative care and instrumentation have greatly improved the morbidity of modern monopolar TURP and make it still useful for our patients.